Clinical profile of dengue infection in a tertiary care hospital - Eregowda, Adarsh; Valliappan, Subramanian (Indian Journal of Child Health, 2015)
Background: Dengue is a major international health concern that is prevalent in tropical and sub-tropical countries. The total burden of febrile illnesses that presents to primary health facilities due to dengue in different parts of Karnataka is largely unknown. Objective: The objective was to study the different clinical manifestations, trend, and outcome of dengue cases admitted in a tertiary care hospital. Materials and Methods: Prospective study conducted over a period of 6 months (July-December 2013) in a tertiary care hospital at Bangalore. Dengue serology was done for all suspected subjects by enzyme-linked immunosorbent assay method. Detailed clinical and demographic details were taken at admission and serial close monitoring for signs and symptoms was done to watch for the progression of the disease. Results: Of the 100 children admitted with probable dengue fever, 57 had confirmed dengue illness. Of these 57 cases, most of the cases were male, and 34 (60%)cases were in age group of 5 months to 15 years with mean age of 7.5±4.7 years. Among the serology confirmed cases, the most common presentation was fever in 57 (100%), followed by abdominal pain in 37 (65%), rashes in 31 (54%), myalgia in 26 (46%), and vomiting in 23 (40%) cases. The most common hemorrhagic manifestation was cutaneous bleeding manifestations like petechiae. Of 57 cases, 46 patients had dengue with no warning signs, 8 had dengue fever with warning signs, and 3 had severe dengue. Conclusion: Clinical manifestations of dengue seem to be changing. Fever, rash, and body ache are still the common manifestations; however, clinicians in the endemic areas should be aware of unusual and novel presentations such as fulminant hepatic failure, splenomegaly, and myocarditis also.